Evaluation of advanced phosphorus removal from slaughterhouse wastewater using industrial waste-based adsorbents - Shengdan Sun (IWA Publishing, 2021)
Slaughterhouse wastewater (SWW) contains high concentrations of phosphorus (P) and is considered as a principal industrial contaminant that causes eutrophication. This study developed two kinds of economical P removal adsorbents using flue gas desulfurization gypsum (FGDG) as the main raw material and bentonite, clay, steel slag and fly ash as the additives. The maximum adsorption capacity of the adsorbent composed of 60% FGDG, 20% steel slag, and 20% fly ash (DSGA2) was found to be 15.85 mg P/g, which was 19 times that of the adsorbent synthesized using 60% FGDG, 30% bentonite, and 10% clay (DSGA1) (0.82 mg P/g). Surface adsorption, internal diffusion, and ionic dissolution co-existed in the P removal process. The adsorption capacity of DSGA2 (2.50 mg P/g) was also evaluated in column experiments. The removal efficiency was determined to be higher than 92% in the first 5 days, while the corresponding effluent concentration was lower than the Chinese upcoming SWW discharge limit of 2 mg P/L. Compared with DSGA1, DSGA2 (synthesized from various industrial wastes) showed obvious advantages in improving adsorption capacity of P. The results showed that DSGA2 is a promising adsorbent for the advanced removal of P from SWW in practical applications. HIGHLIGHTS We developed an efficient granular adsorbent based on industrial waste.; P removal from slaughterhouse wastewater was achieved with reused industrial waste.; Actual treated slaughterhouse wastewater was used in continuous flow experiments.; Surface adsorption, internal diffusion and ionic dissolution played a role in the P removal process.;